Economic growth vs environmental sustainability: examining resource extraction in the World’s largest economies - Zhang, Zhaojin; Zhou, Yanqi (Frontiers in Environmental Science, 2025)
Effective natural resource management is essential for promoting economic stability, environmental sustainability, and long-term global resilience. As the world’s two largest economies, China and the United States play a pivotal role in shaping global resource extraction policies, making it critical to understand the economic and regulatory factors driving their strategies. This study investigates the effects of trade openness, environmental tax, financial depth, and renewable energy consumption on natural resource extraction in both countries. After confirming data stationarity using unit root tests, the analysis employs the bounds testing approach and the Nonlinear Autoregressive Distributed Lag (NARDL) model to ensure robust empirical estimation. The results reveal that financial depth and trade openness are significant drivers of natural resource extraction in both economies, with stronger long-term effects evident in China. Environmental taxes emerge as an effective regulatory mechanism, particularly in the United States, while renewable energy consumption shows a negative but statistically insignificant impact on resource extraction in both contexts. In the short run, trade openness and financial depth consistently promote resource extraction, whereas the effects of environmental taxes and renewable energy consumption vary over different time horizons. These findings highlight the need for integrated, country-specific policy frameworks that balance economic growth with sustainable resource management. The study offers valuable insights for policymakers seeking to align national strategies with global sustainability goals and to strengthen resource governance practices.